Hyperbolic Polaritonic Crystals Based on Nanostructured Nanorod Metamaterials. (28th August 2015) - Dickson, Wayne; Beckett, Stephen; McClatchey, Christina; Murphy, Antony; O'Connor, Daniel; Wurtz, Gregory A.; Pollard, Robert; Zayats, Anatoly V.
<x xml:space="preserve">Abstract</x> Surface plasmon polaritons usually exist on a few suitable plasmonic materials; however, nanostructured plasmonic metamaterials allow a much broader range of optical properties to be designed. Here, bottom‐up and top‐down nanostructuring are combined, creating hyperbolic metamaterial‐based photonic crystals termed hyperbolic polaritonic crystals, allowing free‐space access to the high spatial frequency modes supported by these metamaterials.